2014
DOI: 10.1111/cod.12319
|View full text |Cite
|
Sign up to set email alerts
|

Association between cobalt allergy and dermatitis caused by leather articles – a questionnaire study

Abstract: Our study suggests a positive association between cobalt allergy and a history of dermatitis caused by non-occupational exposure to leather articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The latter correlation between cobalt and shoes is supported by the significant association between foot eczema and cobalt allergy in our study (aOR 2.1, 95%CI: 1.6‐2.9). Similarly, in a case‐control study from Denmark including 126 cobalt‐allergic patients without concomitant hexavalent chromium allergy, a significant association was shown between current foot eczema, presumably caused by leather shoes, and cobalt allergy (aOR 1.9, 95%CI:1.1‐3.3) . Collectively, these data show that cobalt from leather causes allergic cobalt dermatitis, and that leather exposure should be evaluated in patients with cobalt allergy.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The latter correlation between cobalt and shoes is supported by the significant association between foot eczema and cobalt allergy in our study (aOR 2.1, 95%CI: 1.6‐2.9). Similarly, in a case‐control study from Denmark including 126 cobalt‐allergic patients without concomitant hexavalent chromium allergy, a significant association was shown between current foot eczema, presumably caused by leather shoes, and cobalt allergy (aOR 1.9, 95%CI:1.1‐3.3) . Collectively, these data show that cobalt from leather causes allergic cobalt dermatitis, and that leather exposure should be evaluated in patients with cobalt allergy.…”
Section: Discussionmentioning
confidence: 67%
“…We have observed single cases of allergic cobalt dermatitis caused by leather items, but suspect that leather might be a more important source of cobalt exposure than hitherto realized. In this respect, a recent questionnaire case‐control study from our clinic showed that leather was the most frequently reported exposure source causing dermatitis in patients with cobalt allergy without concomitant allergy to hexavalent chromium …”
Section: Introductionmentioning
confidence: 99%
“…Of 291 patients with a positive patch test to cobalt, 135 (46.4%) also had a positive reaction to nickel, confirming that contact sensitization to cobalt is often but not always associated with contact sensitization to nickel and challenging the traditional view of cobalt as a concomitant allergen . Contact sensitization to cobalt in children may result not only from jewelry, but also from toys and leather footwear , as underlined by the association with foot dermatitis.…”
Section: Discussionmentioning
confidence: 96%
“…Simultaneous positive patch test reactions to potassium dichromate, nickel sulfate and cobalt chloride are often reported (17,18). These concurrent reactions are most often explained by multiple sensitization rather than cross-reactivity, and the association between cobalt and Cr(VI) allergy has been attributed to the presence of both metals in both leather and cement (17,18).…”
mentioning
confidence: 99%